Data supporting: 'Development of an environmental hazard-based rating assessment for defence-related chemical compounds in ecological soil systems' - Persico, Federica; Temple, Tracey; Coulon, Frederic; Ladyman, Melissa K. (Cranfield University, 2022)
Environmental hazard-based methods are commonly used to categorise the severity of chemical contamination to ecological soil systems, although a traffic-light approach (green, amber, red) has never been used to assess these consequences. A traffic light approach is an easy to interpretate data as it has a clear visual display which can provide an early warning approach for stakeholders to identify areas that require further investigation. This approach should be underpinned by extensive research data and systematic methods of development. However, the extent of reliable data available for specific chemicals can be limited and therefore decision making may rely on expert judgement. Therefore, in this study, an environmental hazard-based rating methodology was developed by combining the guidelines from the European Chemical Agency (ECHA) and the USEPA for Predicted Non-effect Concentration (PNEC) and Ecological Soil Screening Levels (Eco-SSL) for defence-related chemicals (2,4,6-trinitrotoluene (TNT), 1,3,5-trinitro-1,3,5-triazinane (RDX), cypermethrin, perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS)). The developed hazard-based rating assessment was design to categorise the chemicals into low, medium and high environmental hazards priority to inform and ease the decision-making process for contaminated areas to ensure that sustainable operations are carried out.
Keywords: 'PFOA'; 'PFOS'; 'Cypermethrin'; 'RDX'; 'TNT'; 'Toxicity Scale'; 'Environmental Science'